Social HAZOP at an Oil Refinery. Issue 1 (8th February 2013) - Ávila, S.F.; Pessoa, F.L.P.; Andrade, J.C.S.
<x xml:space="preserve">Abstract</x> Several tools are used in the maintenance of process safety at industry [e.g., Preliminary Risk Analysis (PRA) and Hazards Operation Assessment (HAZOP)]. Each tool or technique can prevent that hazards becoming accidents through project improvements and managerial decisions. The project of equipment and process of chemical industries include technical specifications that work better if human behavior in operation has a pattern without great variations. The HAZOP study indicates top human errors in the control process activities, only identifies common human error of slip (it does not discuss), memory mistake, rules and, consequently, the wrong decision. The Social HAZOP (SH) discusses cognitive processing and the commitment level of the operator in task execution. The SH includes these activities: building of team to investigate human error, identification of critical situations at process with integration with social/human aspects, establish social nodes, analysis of social/human factors, choose items after comparison of standards and subjective measurements, analysis of deviations from social and human processes, recommendations of the SH. An exercise of SH application was done involving level control at separation equipment in a refinery. The recommendations suggest actions in different levels (strategic, tactic, routine, and emergency) and different types (policies, team, managerial aspects, leadership, human and social aspects, stress process at job, risk management, and root cause). © 2013 American Institute of Chemical Engineers Process Saf Prog 32: 17–21, 2013